Possible environmental exposure-associated pulmonary cryptococcosis in a patient with rheumatoid arthritis: a case report and literature review. Issue 10 (October 2020) - Yang, Guangdie; Chen, Junjun; Ye, Jiani; Yao, Yinan; Pan, Zhijie
Patients with rheumatoid arthritis (RA) taking long-term immunosuppressive drugs are more susceptible to opportunistic infections, such as cryptococcosis. A 65-year-old woman was transferred to our hospital for rapidly progressing pulmonary lesions identified by lung computed tomography. She had a 7-year history of RA and had been prescribed methotrexate and glucocorticoids for 10 months. Additionally, our patient had a history of environmental exposure to house renovation lasting approximately 1 week before onset. Her serological test results and histopathological examination confirmed the diagnosis of pulmonary cryptococcosis (PC). The patient recovered well after 6 months of fluconazole treatment. In addition, we summarized 28 reported cases of RA patients with PC and found that older age might be a risk factor for cryptococcal infection in RA patients. The most common location for pulmonary lesions was the lower lobe, and the most common radiologic manifestations were nodules. Detection of cryptococcal capsular polysaccharide antigen was important for diagnosis. Patients undergoing antirheumatic therapy should avoid exposure to Cryptococcus .